The impact of Human resources practices on service quality performance in Saudi Arabia: using structural equation modeling - AL wakeel, Khalid Mohammed; Ibrahim, Siddig Balal (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed at shedding a light of the impact of Human Resources Management Practices on service quality performance in Saudi Arabia. A conceptual model of study was developed. The study population consisted of Saudi service companies. The sample of the study was selected random (non-probable) convenience. The data were collected from service companies in the capital Saudi Arabia Riyadh, with 30 companies, each company included 9 questionnaires distributed to the Human Resources Management Department, with a total distribution of 270 respondents. descriptive analytical approach was adopted, the study found a relationship between human resource practices and the quality of service performance. However, the strength of this relationship varies from one dimension to another, In light of the above results, the study recommended necessary to pay attention to training and development and keep abreast of the latest developments in the training process. The results of this study are important for the service sector in Saudi Arabia as the sector faces increasing competitive pressures in a complex high-growth market. Finally, the study paves the way for further research that will improve the overall performance of organizations through human resource management practices.
Keywords: human resource practices; quality of service performance; structural equation modeling; Saudi Arabia